Evaluation of antioxidant activity in different Egyptian barley cultivars: an in vitro and in silico study - Omneya Eid; Shahira Ezzat; Wafaa M. Elkady; Abeer El Sayed; Essam Abd el-sattar (SpringerOpen, 2024)
Abstract Background Cereals have historically played a crucial role in the human diet, serving as a significant natural source of energy and offering various health benefits. Barley (Hordeum vulgare L.) has been given significant attention in recent years due to its exceptional nutritional value, surpassing that of other cereals. The objective of this research is to evaluate the antioxidant activity of various solvent extracts obtained from three different barley cultivars. Results The G.136 variety's acetone extract exhibited the highest level of antioxidant activity in both the DPPH assay, with an IC50 of 55.62 µg/ml, and the FRAP assay, with 447 μM trolox/mg extract. The dominant compounds identified before in the acetone fraction were subjected to an evaluation of their docking scores, along with an assessment of ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) and TOPKAT (Toxicity Prediction by Komputer Assisted Technology) studies. Notably, hordatine A1, prodelphinidin B3, hordatine B1, procyanidin B2, and isovitexin 7-O-glucoside were the major compounds with the highest LipDock scores compared to trolox the reference drug with polyphenol oxidase. Conclusions The findings indicate that the acetone extract from all three cultivars demonstrates noteworthy results, surpassing the efficacy of other solvent extracts against the antioxidant activity.